Comparison of Individual Penalties According to Gender and Weight Categories of Elite Judo Athletes from Four World Championships - Husnija Kajmovic; Damir Karpljuk; Safet Kapo; Jozef Simenko (Biology, 2022)
Background: This research aimed to compare individual penalties by gender and weight categories in judo from the Judo World Championships (WC): Budapest—2017, Baku—2018, Tokyo—2019 and Budapest—2021 in all individual weight categories for females and males. Methods: Data were collected by notational analysis of 2041 penalty videos for females and 3473 penalty videos for males (total n = 5514). All individual penalties—Shido 1, 2, 3 and Hansoku Make (direct disqualification) were analysed by the Pearson chi-square test at the level of statistical significance of 5%. Results: Significant differences were noted in the assigned individual penalties between individual categories (p < 0.001) in both genders. The significant difference was contributed mainly by the weight category +78 kg with penalties Non-combativity (5.3) and Avoid Grip (−3.4) in females, while in males it impacted by the +100 kg weight category and the Non-combativity (4.2) and Avoid Grip (−4.0) penalties. For females, the most dominant individual penalties were Non-combativity (41.6%), Avoid Grip (16.2%) and False Attack (15.0%), and were Non-combativity (40.3%), Avoid Grip (19.5%) and False Attack (16.4%) for males. The largest number of penalties in females were in −52 kg (16.7%), −57 kg (15.9%) and +78 kg (15.2%) categories, while in males, they were −66 kg (17.2%), −73 kg (16.1%) and −90 kg (15.6%). Conclusions: The findings of this study highlight the leading penalties in all weight categories for both genders on WC to be Non-combativity, Avoid Grip and False Attack. Additionally, a new trend in heavyweight athletes with a lower number of penalties is noted. The obtained results indicate the need to pay more attention to working with competitors of all ages and genders on education to implement tactical variants, forms and means to use penalties to athletes’ advantage, especially after a possible rule change and to lower the occurrence of injuries.